To the theory of spin-charge separation in one-dimensional correlated electron systems - Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Spin—charge separation is considered to be one of the key properties that distinguish low-dimensional electron systems from others. Three-dimensional correlated electron systems are describedby the Fermi liquid theory. There, low-energy excitations (quasiparticles) are reminiscentof noninteracting electrons: They carry charges -e and spins 1/2 . It is believed that for any one-dimensional correlated electron system, low-lying electron excitations carry either only spin and no charge, or only charge without spin. That is why recent experiments looked for such low-lying collectiveelectron excitations, one of which carries only spin, and the other carries only charge. Here we show that despite the fact that for exactly solvable one-dimensional correlated electron models there exist excitations which carry only spin and only charge, in all these models with short-range interactions the low-energy physics is described by low-lying collective excitations, one of whichcarries both spin and charge.